Learning To Foster The Culture Of Science Literacy In State Elementary School Of Demangan Yogyakarta - Hayaturraiyan Hayaturraiyan (AIUA Journal of Islamic Education, 2020)
Science literacy needs to be cultivated since elementary school (SD/MI) considering that science is a science that is always developing so students are not left behind by the times. In Indonesia, the educational realm of scientific literacy skills is explicitly taught in science/IPA lessons. To optimize scientific literacy skills, communicative interaction between teacher and students is needed during the learning process. Through interaction and strong communication between teachers and students, it has an impact on the occurrence of quality and effective learning. SD Negeri Demangan Yogyakarta is one of the schools that began to apply a culture of scientific literacy. Besides that, the interaction in the learning process seemed active. Therefore this study aims to find out and explain the culture of scientific literacy in SD Negeri Demangan Yogyakarta and to find out and explain learning interactions to foster a culture of scientific literacy in SD Negeri Demangan Yogyakarta.This research belongs to the case study qualitative research, located in the State in SD Negeri Demangan Yogyakarta. Data collection uses in-depth interviewing, observation, and documentation techniques. Data analysis uses the Miles and Huberman models with the stages of data reduction, then presents the data, and ends with concluding. Checking the validity of the data is done by triangulation of techniques and sources, by checking the findings from the results of interview techniques, observation, and documentation, and checking findings based on the main sources of research. The results of this study indicate that: (1) the culture of scientific literacy in SD Negeri Demangan Yogyakarta has begun to run, it can be seen from the existing facilities and infrastructure and activities carried out by teachers and students. (2) learning interactions to foster a culture of scientific literacy have been seen in the preparation and implementation of the science/IPA learning interaction process.